ANALISIS PLANNING, ORGANIZING, ACTUATING, DAN CONTROLLING PADA PENGELOLAAN PROGRAM MUDIK GRATIS SULAWESI TENGGARA 2026 - Maudhy Satyadharma; Rina Sutriana; Sylsiani Mursalim; Patta Hindi Asiz (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2025)
The free homecoming ticket program is a strategic policy implemented by the regional government to improve public welfare, particularly during religious holidays such as Eid al-Fitr. This study aims to analyze the management of the free homecoming ticket program in Southeast Sulawesi Province through the Planning, Organizing, Actuating, and Controlling (POAC) management function approach, integrated with collaborative governance and good governance perspectives. The research method used was qualitative with a descriptive-analytical approach. Data collection techniques included interviews, observation, and documentation. The results indicate that the planning aspect has been carried out systematically, but still faces challenges in data accuracy. In terms of organization, collaboration between stakeholders has been established but is not yet optimal. In terms of implementation, the program is running effectively, but technical operational challenges remain. In terms of supervision, an evaluation mechanism has been implemented but is not yet based on comprehensive performance indicators. The integration of collaborative governance and good governance principles has been proven to increase program effectiveness. This study recommends strengthening digitalization, increasing cross-sector synergy, and developing a performance-based evaluation system.